American Association for the Surgery of Trauma/American College of Surgeons Committee on Trauma clinical protocol for nutrition support in adult trauma - Julie Valenzuela; Krista Haines; Gaurav Sachdev; Cassandra White; Thomas Schroeppel; Tanya Anand; Shannon L. Castle; Lena M. Napolitano (Journal of Trauma and Acute Care Surgery, 2026)
ABSTRACT: The provision of nutrition in adult trauma patients requires a detailed and personalized approach to achieve optimal patient outcomes. Initial assessment for malnutrition is required in all patients, as the hypermetabolic state of acute trauma may exacerbate malnutrition risk during the acute phase. Initial assessment in ICU patients includes determination of nutrition risk (high vs. low) using the modified NUTRIC or NRS scores and evaluation for malnutrition. In critically ill trauma patients, indirect calorimetry is most accurate for determination of calorie/protein requirements. Early enteral nutrition is recommended when resuscitation is complete. Continuous gastric feeds are recommended, with postpyloric jejunal feeding for patients at high risk of aspiration. In patients with enteral feeding intolerance and ileus, prokinetic agents should be implemented first, followed by postpyloric feeding tube if persistent feeding intolerance. Parenteral nutrition should be initiated if enteral nutrition is contraindicated (intestinal obstruction, severe ileus, high-output fistula, ischemia), and in patients who cannot achieve goal enteral nutrition. In patients with shock requiring vasopressors, an individualized approach should evaluate the risks and benefits of early enteral nutrition versus the potential risk of nonocclusive mesenteric ischemia. Critically ill geriatric, obese, and cirrhotic trauma patients warrant specialized nutrition care. Immunonutrition, glutamine, and probiotics/prebiotics are not currently recommended for trauma or burn patients. (J Trauma Acute Care Surg. 2026; 00:000–000 Copyright © 2026 Wolters Kluwer Health, LLC. All rights reserved.) LEVEL OF EVIDENCE: Therapeutic/care management; Level V.